Tunable Perpendicular Magnetoresistive Sensor Driven by Shape and Substrate Induced Magnetic Anisotropy (Adv. Sensor Res. 2/2023). Issue 2 (10th February 2023) - Barrera, Aleix; Fourneau, Emile; Martín, Sergi; Batllori, Josep Maria; Alcalá, Jordi; Balcells, Lluís; Mestres, Narcís; Nguyen, Ngoc Duy; Sanchez, Alvaro; Silhanek, Alejandro V.; Palau, Anna
Abstract : Tunable Magnetoresistive Sensors In article number 2200042, Alejandro V. Silhanek, Anna Palau, and co‐workers study permalloy strips with substrate‐induced uniaxial anisotropy since they offer the possibility to produce fast in‐plane magnetization reversals triggered by an out‐of‐plane magnetic field. Sharp magnetoresistance jumps tailored by the shape anisotropy of the strips are obtained and are potentially useful for sensing and advanced magnetoresistive devices.